DIFFERENTIAL ITEM FUNCTIONING ANALYSIS, AN ISSUE ON UMPTN ITEM BANKING WITH IRT PROCEDURES - Saifuddin Azwar (Buletin Psikologi, 1994)
National College Admission Test (Ujian Masuk Perguruan Tinggi Negeri - UMPTN) was first administered to select candidates for five most prominent universities in Indonesia more than fifteen years ago. The system was then improved and has been widely used with the inclusion of more than 10 participating universities across the country.